Market making and the (re)production of knowledge in public universities. Issue 3 (1st December 2022) - Lewis, Nick; Robertson, Susan; Lim, Miguel Antonio; Komljenovic, Janja; Muellerleile, Chris; Shore, Cris; Bajenova, Tatyana
Abstract: This collection of short essays presents and examines six vignettes of organisational change in British, New Zealand and European universities. Drawing on the social studies of economisation literature, formal research projects and auto-ethnographic insights, the authors detail profound changes in how knowledge is produced in universities. They examine policy documents, calculative techniques and management practices to illustrate how proliferating market rationalities, technologies and relations are reimagining university missions, reframing their practices and refashioning their subjects. Their vignettes demonstrate that market-making pressures are emerging from micro-scale socio-technical arrangements as well as altered funding models and external policy imperatives. They reveal the extent and detail of market-making pressures on academic practice in research and teaching. Finding ways to contest these pressures is imperative.